Penyuluhan Ibu Hamil Melalui Pelayanan Antenatal Care Untuk Mencegah Kurang Energi Kronik - Pomarida Simbolon; Nagoklan Simbolon; Adrian Hutauruk; Scere Sophia Sitorus; Agnes Jeane Zebua (Perigel: Jurnal Penyuluhan Masyarakat Indonesia, 2023)
Antenatal Care (ANC) is the most important component of pregnant women's health services to reduce maternal and infant mortality rates. With ANC, the progress of the pregnant woman's condition will be well monitored at all times and knowledge about childbirth preparation will increase. Based on the background above, the researcher is interested in taking the title Counseling Pregnant Women Through Antenatal Care Services to Prevent Chronic Energy Deficiency which aims to improve and maintain the health of mothers and babies, prepare for the birthing process so that the baby can be delivered safely and minimize trauma that may occur in the child. during childbirth and reduce the number of deaths and morbidity rates in mothers. The data collection method that the author uses is the survey method. The survey method is a method used as a general category of research, one of which uses a questionnaire. The research results showed that the average knowledge score before and after the health education was carried out increased by 42.21 points, which means that the health education carried out had an impact on increasing the knowledge of Health Information Management students about ANC disease in pregnant women who experience CED. The increase in the average knowledge score is possible because health education uses appropriate methods and media such as lectures and discussions. Leaflet media also helps health education participants to easily remember the material. Using appropriate methods and media in health education can help health education participants understand the material